2013
DOI: 10.1021/am400460p
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diffusivity of Hexagonal Boron Nitride Composites Based on Cross-Linked Liquid Crystalline Polyimides

Abstract: Hexagonal boron nitride (h-BN) composites with the oriented cross-linked liquid crystalline (LC) polyimide have been developed as high thermally conductive materials. Well-dispersed h-BN composite films were obtained, as observed by scanning electron microscopy. The morphology of the composite films was further investigated in detail by the wide-angle X-ray diffraction. The obtained composite films based on the cross-linked LC polyimide showed that the polymer chains vertically aligned in the direction paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…7(b)). 24 The diffraction images of the composite lms are presented in Fig. 7(c), which shows diffraction peaks assignable to (100), (002), (101), (102), (110) and (103) diffraction.…”
Section: Tcs Of Pi Blend Composite Lmsmentioning
confidence: 99%
“…7(b)). 24 The diffraction images of the composite lms are presented in Fig. 7(c), which shows diffraction peaks assignable to (100), (002), (101), (102), (110) and (103) diffraction.…”
Section: Tcs Of Pi Blend Composite Lmsmentioning
confidence: 99%
“…The effect of polymeric matrices and their orientations on the thermal transport performance of the composites with BNNs have also been considered 74. 75 For example, in the work by Shoji et al,74 oriented cross‐linked liquid‐crystalline polyimide was used as a matrix for thermally conductive composites with BNNs.…”
Section: Thermally Conductive Nanocompositesmentioning
confidence: 99%
“…The effect of polymeric matrices and their orientations on the thermal transport performance of the composites with BNNs have also been considered 74. 75 For example, in the work by Shoji et al,74 oriented cross‐linked liquid‐crystalline polyimide was used as a matrix for thermally conductive composites with BNNs. The observed thermal diffusivity in these composites was in the order of 0.68 mm 2 s −1 at a 30 vol % h‐BN loading, which was somewhat higher (about 10 %) than that in the composites made with amorphous polyimide 74.…”
Section: Thermally Conductive Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] The mechanical properties of their nanocomposites is enhanced by various functional groups such as amines, nitriles, epoxides, and oxides [21][22][23] due to improvement in their dispersion in polymer matrices that facilitate better polymer-nanomaterial interaction and allow efficient load transfer from the polymer to the nanomaterial. 19 Additionally, it has been reported that presence of boron nitride nanomaterials (specifically exfoliated boron nitride nanosheets 24 ) improves the thermal conductivity of polymers, and therefore, may be beneficial for in situ thermal crosslinking of injectable polymer mixtures.…”
Section: Introductionmentioning
confidence: 99%